Heat transfer suppressing sheet and battery pack
By using inorganic fibers and organic fibers to interweave them in the insulating sheet to form a three-dimensional network structure and air layer, and fixing inorganic particles through the welding part, the strength and dispersion of the insulating sheet under compressive stress is solved, and efficient heat transfer suppression is achieved and improve thermal insulation performance.
Patent Information
- Application Number
- CN202380042158.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-27
- Filing Date
- 2023-05-26
- Publication Date
- 2025-01-14
AI Technical Summary
The strength of existing insulation sheets decreases under compression stress, resulting in powder falling off, unable to effectively inhibit heat transfer, and dry silica aerogels are difficult to disperse, resulting in a degradation of thermal insulation performance.
The organic fibers and inorganic fibers in the matrix containing inorganic particles are interwoven to form a three-dimensional network structure to form an air layer, and the inorganic particles are fixed through the welding part to improve the strength and dispersion of the insulating sheet and prevent the powder from falling off.
The shape maintenance of the insulating sheet under compressive stress and the insulation performance optimization are achieved, which effectively suppresses heat transfer, prevents thermal chaining, and improves the safety of the battery pack.
Smart Images

Figure CN119318061A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heat transfer suppressing sheet and a battery pack having the same. Background Art
[0002] In recent years, from the perspective of environmental protection, electric vehicles and hybrid vehicles driven by electric motors have been actively developed. These electric vehicles and hybrid vehicles are equipped with a battery pack composed of a plurality of battery cells connected in series or in parallel to serve as a power source for the driving electric motor.
[0003] In addition, the battery cells mainly use lithium-ion secondary batteries that have higher capacity and higher output than lead-acid batteries, nickel-metal hydride batteries, etc. Moreover, in the case of thermal runaway such as a battery cell rapidly heating up and then continuously releasing heat due to internal short circuits, overcharging, etc. of the battery, the heat from the battery cell that has thermal runaway is transmitted to other adjacent battery cells, which may cause thermal runaway of other battery cells.
[0004] As a method of suppressing the propagation of heat from a battery cell that has undergone thermal runaway as described above, a method of interposing a heat insulating sheet between battery cells is generally performed.
[0005] For example, Patent Document 1 discloses a thermal insulation sheet for a battery pack, which includes first particles composed of silica nanoparticles and second particles composed of metal oxides, and the content of the first particles is limited. In addition, Patent Document 1 states that the thermal insulation sheet may include a binding material composed of at least one selected from fibers, adhesives, and heat-resistant resins.
[0006] Furthermore, Patent Document 1 describes that dry silica or wet silica can be used as the first particles, and that the thermal insulation sheet can be produced by a dry molding method or a wet papermaking method.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2021-34278 Summary of the invention
[0010] Problems to be solved by the invention
[0011] In addition, as an adhesive for manufacturing the thermal insulation sheet (heat transfer suppression sheet), for example, a wet heat adhesive fiber can be cited, but the wet heat adhesive fiber needs to be in a wet state during manufacturing in order to exhibit its adhesiveness. Therefore, when using the wet heat adhesive fiber, the thermal insulation sheet needs to be manufactured by a wet papermaking method.
[0012] However, in the case of using dry silica or silica aerogel with low thermal conductivity for the purpose of further improving thermal insulation performance, there is a problem that the thermal insulation sheet cannot be manufactured by the wet papermaking method. This is because if the material containing dry silica is formed into a sheet by the wet papermaking method, the dry silica will condense due to water, and the thermal conductivity will increase. In addition, silica aerogel is generally difficult to disperse in water, so if the material containing silica aerogel is formed by the wet papermaking method, it is impossible to obtain a thermal insulation sheet in which the material is uniformly dispersed, which becomes a cause of quality reduction.
[0013] On the other hand, when an insulating sheet is manufactured by a dry molding method using inorganic particles such as dry silica or silica aerogel, the inorganic particles may sometimes fall off (hereinafter also referred to as powder falling off) due to pressure, impact, etc. In particular, in battery packs in recent years, the capacity of battery cells has been further improved, so the expansion rate during charging and discharging has increased. Therefore, in the case where the insulating sheet is arranged between battery cells in the battery pack, if the overall strength of the insulating sheet is low, the insulating sheet is compressed and powder falls off due to the expansion of the battery cells during charging and discharging of the battery cells, and the thermal insulation performance is reduced. As a result, when the battery cells undergo thermal runaway and reach a high temperature, the effect of the insulating sheet cannot be exerted, and sometimes a thermal chain reaction occurs. Based on this, it is required to develop an insulating sheet and a method for manufacturing the same that has high strength that can continuously maintain its shape, can suppress powder falling off, and can maintain excellent thermal insulation.
[0014] The thermal insulation sheet described in Patent Document 1 can maintain excellent thermal insulation even when the compressive stress increases, but further improvements are required in terms of thermal insulation, strength, and performance to suppress powder shedding.
[0015] The present invention has been completed in view of the above-mentioned problems, and its purpose is to provide a heat transfer suppression sheet and a battery pack having the heat transfer suppression sheet, wherein the heat transfer suppression sheet has strength that can maintain its shape even when compressive stress is applied to the heat transfer suppression sheet, and has high inorganic particle retention performance, thereby maintaining excellent insulation performance.
[0016] Means for solving problems
[0017] The above object of the present invention is achieved by the following configuration [1] of the heat transfer suppressing sheet.
[0018] [1] A heat transfer suppressing sheet comprising a matrix containing inorganic particles, inorganic fibers dispersed in the matrix, and organic fibers, wherein the organic fibers and the inorganic fibers are intertwined to form a three-dimensional network structure.
[0019] In addition, preferred embodiments of the heat transfer suppressing sheet of the present invention relate to the following [2] to
[11] .
[0020] [2] The heat transfer suppressing sheet according to [1], wherein the substrate has an air layer around the inorganic fibers.
[0021] [3] The heat transfer suppressing sheet according to [1] or [2], characterized in that:
[0022] The organic fiber has a fusion bond covering at least a portion of the surface.
[0023] At least a portion of the inorganic fibers is fused to the organic fibers via the fusion portion.
[0024] [4] The heat transfer suppressing sheet according to [3], wherein at least a portion of the inorganic particles are fused to the organic fibers via the fusion portion.
[0025] [5] The heat transfer suppressing sheet according to [3] or [4], characterized in that:
[0026] The organic fiber is formed of a first organic material, and the welded portion includes a second organic material.
[0027] The second organic material has a melting point lower than that of the first organic material.
[0028] [6] The heat transfer suppressing sheet described in [5] is characterized in that the melting point of the second organic material is lower than the melting point of the first organic material by at least 60°C.
[0029] [7] The heat transfer suppressing sheet according to [5] or [6], characterized in that:
[0030] The first organic material is at least one selected from polyethylene terephthalate, polypropylene and nylon.
[0031] The second organic material is at least one selected from polyethylene terephthalate, polyethylene, polypropylene and nylon.
[0032] [8] The heat transfer suppressing sheet according to any one of [1] to [7], wherein the inorganic particles include at least one particle selected from oxide particles, carbide particles, nitride particles, and inorganic hydrate particles.
[0033] [9] The heat transfer suppressing sheet according to [8], wherein the inorganic particles include at least one particle selected from dry silica particles and silica aerogel.
[0034]
[10] The heat transfer suppressing sheet described in [9] is characterized in that the inorganic particles further include particles composed of at least one inorganic material selected from titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide and aluminum oxide.
[0035]
[11] A heat transfer suppression sheet as described in any one of [1] to
[10] , characterized in that the above-mentioned inorganic fiber is at least one fiber selected from silica-alumina fiber, alumina fiber, silica fiber, rock wool, alkaline earth silicate fiber and glass fiber.
[0036] In addition, the above-mentioned object of the present invention is achieved by the following
[12] structure of the battery pack.
[0037]
[12] A battery pack comprising a plurality of battery cells and the heat transfer suppressing sheet according to any one of [1] to
[11] , wherein the plurality of battery cells are connected in series or in parallel.
[0038] Effects of the Invention
[0039] The heat transfer suppression sheet of the present invention comprises inorganic fibers and organic fibers dispersed in a matrix containing inorganic particles. The organic fibers and the inorganic fibers are interwoven with each other to form a three-dimensional network structure, thereby obtaining excellent strength, thereby suppressing powder shedding and preventing a reduction in the insulation effect due to compression deformation of the heat transfer suppression sheet.
[0040] According to the battery pack of the present invention, since the heat transfer suppression sheet having the effect of maintaining high strength and heat insulation performance as described above is provided, thermal runaway of battery cells in the battery pack can be suppressed and spread of flames to the outside of the battery case can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 It is a schematic diagram showing the structure of the heat transfer suppression sheet according to the embodiment of the present invention.
[0042] Figure 2 It is enlarged to show Figure 1 Schematic diagram of portion A of the heat transfer suppression sheet shown.
[0043] Figure 3 : is a cross-sectional view schematically showing a battery pack including a heat transfer suppressing sheet according to an embodiment of the present invention. DETAILED DESCRIPTION
[0044] The present inventors have conducted intensive studies on a heat transfer suppressing sheet that can solve the above-mentioned problems.
[0045] As a result, the inventors have found that when organic fibers and inorganic fibers are intertwined with each other to form a three-dimensional network structure in a matrix containing inorganic particles, the strength of the heat transfer suppressing sheet can be increased, thereby maintaining high thermal insulation performance.
[0046] The heat transfer suppression sheet, its manufacturing method and battery pack according to the embodiments of the present invention are described in detail below. It should be noted that the present invention is not limited to the embodiments described below, and can be implemented with any modifications within the scope of the present invention.
[0047] [Heat transfer suppression sheet]
[0048] Figure 1 It is a schematic diagram showing the structure of the heat transfer suppression sheet according to the embodiment of the present invention. Figure 2 It is enlarged to show Figure 1 Schematic diagram of the A portion of the heat transfer suppression sheet shown. Figure 3 : is a cross-sectional view schematically showing a battery pack including a heat transfer suppressing sheet according to an embodiment of the present invention.
[0049] like Figure 1 and Figure 2 As shown, the heat transfer suppression sheet 10 of this embodiment has a matrix 14 containing inorganic particles 4, inorganic fibers 15 dispersed in the matrix 14, and organic fibers 1. In addition, the organic fibers 1 and the inorganic fibers 15 are intertwined to form a three-dimensional network structure. It should be noted that in this embodiment, an air layer 18 is formed in a part of the periphery of the inorganic fibers 15. In addition, the organic fiber 1 has a fusion bond 5 on a part of the surface, and at least a part of the inorganic fiber 15 is fused to the organic fiber 1 through the fusion bond 5. In addition, at least a part of the inorganic particles 4 is fused to the organic fiber 1 through the fusion bond 5.
[0050] It should be noted that, in this specification, the inorganic fibers 15 are “dispersed”, which means that the inorganic fibers 15 are not extremely concentrated but are arranged throughout the entire body.
[0051] As a specific use of the heat transfer suppression sheet 10, Figure 3 As shown, the heat transfer suppression sheet 10 can be used in a manner where a plurality of battery cells 20a, 20b, 20c are sandwiched. In addition, the plurality of battery cells 20a, 20b, 20c are connected in series or in parallel (the connection state is not shown), and are housed in a battery case 30 to form a battery pack 100. It should be noted that the battery cells 20a, 20b, 20c are suitable for lithium-ion secondary batteries, but are not particularly limited thereto, and can also be applied to other secondary batteries.
[0052] In the heat transfer suppression sheet 10 of the present embodiment configured as above, the organic fibers 1 and the inorganic fibers 15 are interwoven to form a three-dimensional network structure, and this structure serves as a skeleton, so that high strength can be obtained. Therefore, even when the heat transfer suppression sheet is compressed by the expansion of the battery cells 20a, 20b, and 20c during charge and discharge, the shape can be maintained, the inorganic particles 4 can be suppressed from falling off (powder falling off), and the reduction of the heat insulation effect due to the compression deformation of the heat transfer suppression sheet 10 can be prevented.
[0053] In addition, since the heat transfer suppression sheet 10 of the present embodiment includes the organic fiber 1 having high flexibility, the flexibility of the heat transfer suppression sheet 10 can be improved, and the organic fiber 1 can be easily entangled with the inorganic fiber 15 to form a three-dimensional network structure, and the sheet strength can also be improved. On the other hand, if the heat transfer suppression sheet 10 does not include the inorganic fiber 15, for example, when the battery cell 20a undergoes thermal runaway and the heat transfer suppression sheet 10 arranged adjacent to the battery cell 20a is exposed to high temperature, the organic fiber 1 decomposes and the shape of the heat transfer suppression sheet 10 cannot be maintained. Therefore, by making the heat transfer suppression sheet 10 contain the organic fiber 1 having high flexibility and the inorganic fiber 15 that does not decompose even at high temperatures, both characteristics of flexibility and strength can be well balanced.
[0054] In addition, in the present embodiment, an air layer 18 is provided around the inorganic fibers 15 dispersed in the matrix 14. The thermal conductivity of the inorganic fibers 15 is higher than that of the organic fibers 1, but as described above, by forming the air layer 18 around the inorganic fibers 15, heat transfer between the inorganic fibers 15 and the matrix 14 can be suppressed. It should be noted that the air layer 18 is formed in the manufacturing process of the heat transfer suppression sheet 10 described later, but the air layer 18 does not need to be formed in the entire area around the inorganic fibers 15. As long as the air layer 18 is formed on at least a portion of the outer peripheral surface of the inorganic fibers 15, the heat transfer suppression effect can be obtained.
[0055] If the inorganic fibers 15 are uniformly dispersed in the matrix 14 , the air layer 18 in the matrix 14 is also uniformly dispersed and arranged, so that the heat transfer suppressing sheet 10 can obtain high thermal insulation without unevenness.
[0056] In addition, in this embodiment, the organic fiber 1 has a fusion bond 5 covering at least a portion of the surface. The fusion bond 5 is a portion where the surface of the organic fiber 1 is melted and then solidified again, and is formed in the manufacturing process of the heat transfer suppression sheet 10 described later. When at least a portion of the inorganic fiber 15 is fused to the organic fiber 1 by the fusion bond 5, the organic fiber 1 and the inorganic fiber 15 intertwined with each other are fixed, so that a heat transfer suppression sheet 10 with further high strength can be obtained.
[0057] Similarly, in this embodiment, the inorganic particles 4 are also fixed to the organic fibers 1 by the welded portions 5 on the outer peripheral surface of the organic fibers 1, so that a higher powder fall-off suppression effect can be obtained. Therefore, even if, for example, a part of the battery cells 20a, 20b, 20c expands and applies compressive stress or impact to the heat transfer suppression sheet 10, excellent thermal insulation performance can be maintained.
[0058] In the present embodiment, as a mechanism for suppressing the inorganic particles 4 from falling off from the sheet surface, as described above, it is considered that the organic fibers 1 and the inorganic fibers 15 are fused together by the fusion bond portion 5 to form a strong three-dimensional framework, which can maintain the shape of the heat transfer suppression sheet 10 and suppress deformation or compression of the heat transfer suppression sheet 10. In addition, it is considered that the organic fibers 1 and the inorganic fibers 15 exposed on the sheet surface can absorb the impact given to the heat transfer suppression sheet 10, which is also the reason why the inorganic particles 4 can be retained.
[0059] It should be noted that Figure 2 In the embodiment, the inorganic particles 4 are welded to the entire outer peripheral surface of the organic fiber 1 through the welded portion 5, but in the present invention, the welded portion 5 does not have to completely cover the outer peripheral surface of the organic fiber 1, and there may be a local area where the welded portion 5 does not exist. In the heat transfer suppressing sheet 10 of this embodiment, as a material of the organic fiber 1, an adhesive fiber of a core-sheath structure described later can be used. In this case, if the sheath portion is peeled off during the manufacturing process, the organic fiber 1 as the core portion may be partially exposed. Even in such a case, the effect of retaining the inorganic particles 4 can be fully obtained.
[0060] The materials constituting the heat transfer suppressing sheet of the present embodiment will be described in detail below.
[0061] <Organic Fiber>
[0062] The organic fiber 1 imparts flexibility to the heat transfer suppression sheet 10, and has the effect of maintaining the strength and shape of the sheet by fusing the inorganic particles 4 and the inorganic fiber 15 on its surface. As the material of the organic fiber 1 in the heat transfer suppression sheet 10, a single-component organic fiber may be used, but it is preferred to use an adhesive fiber with a core-sheath structure. The adhesive fiber with a core-sheath structure has a core extending in the longitudinal direction of the fiber, and a sheath formed in a manner covering the outer peripheral surface of the core. In addition, the core is composed of a first organic material, and the sheath is composed of a second organic material, and the melting point of the first organic material is higher than that of the second organic material. In the case of using an adhesive fiber with a core-sheath structure as a material, in the above-mentioned heat transfer suppression sheet 10, the core is equivalent to the organic fiber 1. In addition, when the heat transfer suppression sheet 10 is manufactured, the second organic material constituting the sheath is melted and then solidified again, so in the heat transfer suppression sheet 10, the sheath becomes the fusion bond 5.
[0063] When a core-sheath structured binder fiber is used as the material of the organic fiber 1, there is no particular limitation as long as the core portion, i.e., the first organic material constituting the organic fiber 1, has a higher melting point than the sheath portion, i.e., the second organic material, present on the outer peripheral surface of the organic fiber 1. The first organic material may be at least one selected from polyethylene terephthalate, polypropylene, and nylon.
[0064] (Organic fiber content)
[0065] In the present embodiment, if the content of the organic fiber 1 in the heat transfer suppressing sheet 10 is appropriately controlled, a sufficient reinforcement effect of the skeleton can be obtained.
[0066] The content of the organic fiber 1 is preferably 2% by mass or more, and more preferably 4% by mass or more, relative to the total mass of the heat transfer suppression sheet 10. In addition, if the content of the organic fiber 1 is too much, the content of the inorganic particles 4 is relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of the organic fiber is preferably 10% by mass or less, and more preferably 8% by mass or less, relative to the total mass of the heat transfer suppression sheet 10.
[0067] (Fiber length of organic fibers)
[0068] The fiber length of the organic fibers 1 is not particularly limited, but the average fiber length of the organic fibers is preferably 10 mm or less from the viewpoint of ensuring moldability and processability.
[0069] On the other hand, from the viewpoint of allowing the organic fibers 1 to function as a skeleton and ensuring the compressive strength of the heat transfer suppressing sheet, the average fiber length of the organic fibers 1 is preferably 0.5 mm or more.
[0070] <Welding section>
[0071] The welded portion 5 is formed by temporarily melting the surface of the organic fiber 1 or the sheath of the binder fiber having a core-sheath structure by heating and then cooling it, so that the inorganic particles 4 and the inorganic fibers 15 are welded to the surface of the organic fiber 1. When a binder fiber having a core-sheath structure is used as the material of the organic fiber 1, the welded portion 5 contains a second organic material constituting the sheath.
[0072] (Second organic material)
[0073] The second organic material is not particularly limited as long as it has a lower melting point than the first organic material constituting the organic fiber 1. The second organic material may be at least one selected from polyethylene terephthalate, polyethylene, polypropylene, and nylon.
[0074] The melting point of the second organic material is preferably 90° C. or higher, more preferably 100° C. or higher. The melting point of the second organic material is preferably 150° C. or lower, more preferably 130° C. or lower.
[0075] <Inorganic particles>
[0076] As inorganic particles, single inorganic particles can be used, and more than two kinds of inorganic particles can also be used in combination. As the kind of inorganic particles, from the aspect of the heat transfer inhibition effect, preferably use the particles consisting of at least one inorganic material selected from oxide particles, carbide particles, nitride particles and inorganic hydrate particles, more preferably use oxide particles. In addition, there is no particular limitation on shape, preferably comprising at least one selected from nanoparticles, hollow particles and porous particles, specifically, inorganic hollow balls such as silicon dioxide nanoparticles, metal oxide particles, microporous particles, hollow silicon dioxide particles, particles consisting of thermally expansive inorganic materials, particles consisting of water-containing porous bodies, etc. can also be used.
[0077] If the average secondary particle size of the inorganic particles is 0.01 μm or more, it is easy to obtain and the increase in manufacturing cost can be suppressed. In addition, if it is 200 μm or less, the desired insulation effect can be obtained. Therefore, the average secondary particle size of the inorganic particles is preferably 0.01 μm or more and 200 μm or less, and more preferably 0.05 μm or more and 100 μm or less.
[0078] It should be noted that, if two or more inorganic particles with different heat transfer inhibition effects are used together, the exothermic body can be cooled in multiple stages, and endothermic effect can be shown in a wider temperature range. Specifically, it is preferred that large-diameter particles and small-diameter particles are mixed and used. For example, when using nanoparticles as inorganic particles on one side, inorganic particles as the other side preferably include inorganic particles consisting of metal oxides. Hereinafter, the inorganic particles with small diameter are used as the first inorganic particles and the inorganic particles with large diameter are used as the second inorganic particles, and the inorganic particles are further described in detail.
[0079] <First Inorganic Particles>
[0080] (Oxide particles)
[0081] The refractive index of oxide particles is high, and the effect of diffuse reflection of light is strong. Therefore, when oxide particles are used as the first inorganic particles, radiative heat transfer can be suppressed, especially in high temperature areas such as abnormal heat release. As oxide particles, at least one particle selected from silica, titania, zirconium oxide, zircon, barium titanate, zinc oxide and aluminum oxide can be used. That is, among the above-mentioned oxide particles that can be used as inorganic particles, only one type can be used, or two or more types of oxide particles can be used. In particular, silica is a component with high thermal insulation, and titania is a component with a higher refractive index than other metal oxides. It is highly effective in diffuse reflection of light and shielding radiant heat in high temperature areas above 500°C, so it is most preferred to use silica and titania as oxide particles.
[0082] (Average primary particle size of oxide particles: 0.001 μm or more and 50 μm or less)
[0083] The particle size of the oxide particles may affect the effect of reflecting radiant heat. Therefore, if the average primary particle size is limited to a predetermined range, a higher thermal insulation property can be obtained.
[0084] That is, if the average primary particle size of the oxide particles is greater than 0.001 μm, it is sufficiently larger than the wavelength of light that contributes to heating, so that the light is efficiently diffusely reflected. Therefore, in the high temperature region above 500°C, the radiation heat transfer in the heat transfer suppression sheet is suppressed, and the thermal insulation can be further improved.
[0085] On the other hand, if the average primary particle size of the oxide particles is less than 50 μm, the number of contacts between the particles will not increase even if compressed, making it difficult to form a path for conductive heat transfer. This can particularly reduce the impact on the insulation in the normal temperature range where conductive heat transfer dominates.
[0086] In the present invention, the average primary particle size can be determined by observing the particles with a microscope, comparing with a standard scale, and taking the average of any 10 particles.
[0087] (Nanoparticles)
[0088] In the present invention, nanoparticles refer to nano-scale particles with a spherical or nearly spherical average primary particle size of less than 1 μm. Since nanoparticles are low-density, conductive heat transfer can be suppressed. If nanoparticles are used as the first inorganic particles, the voids are further finely dispersed, so that excellent thermal insulation that suppresses convective heat transfer can be obtained. Therefore, when a battery is used in a normal temperature range, heat conduction between adjacent nanoparticles can be suppressed. From this aspect, nanoparticles are preferably used.
[0089] In addition, when nanoparticles with a small average primary particle size are used as oxide particles, even when the heat transfer suppression sheet is compressed due to expansion associated with thermal runaway of the battery cell and the internal density increases, the increase in conductive heat transfer of the heat transfer suppression sheet can be suppressed. It is believed that the reason for this is that nanoparticles easily form fine gaps between particles due to electrostatic repulsion, and the packing density is low, so the particles are filled in a manner having a buffering property.
[0090] It should be noted that in the present invention, when nanoparticles are used as the first inorganic particles, there is no particular limitation on the material as long as it meets the above definition of nanoparticles. For example, silicon dioxide nanoparticles are highly thermally insulating materials, and the contact points between the particles are small, so the heat conducted by the silicon dioxide nanoparticles is less than that when using silicon dioxide particles with a large particle size. In addition, the bulk density of the silicon dioxide nanoparticles usually obtained is 0.1 (g / cm 3 ), so for example, even if the battery cells arranged on both sides of the heat transfer suppression sheet undergo thermal expansion and a large compressive stress is applied to the heat transfer suppression sheet, the size (area) and number of the contact points between the silica nanoparticles will not increase significantly, and the thermal insulation can be maintained. Therefore, as nanoparticles, silica nanoparticles are preferably used. Examples of silica nanoparticles include wet silica, dry silica, and aerogel, and silica nanoparticles particularly suitable for this embodiment are described below.
[0091] Generally, wet silica particles aggregate, whereas dry silica particles can be dispersed. In the temperature range below 300°C, heat conduction is dominant, so dry silica particles that can be dispersed can achieve superior thermal insulation performance compared to wet silica.
[0092] It should be noted that the heat transfer suppressing sheet of the present embodiment is preferably produced by a method of processing a mixture containing materials into a sheet by a dry method. Therefore, dry silica, silica aerogel, etc. having low thermal conductivity are preferably used as inorganic particles.
[0093] (Average primary particle size of nanoparticles: 1 nm or more and 100 nm or less)
[0094] When the average primary particle size of the nanoparticles is limited to a predetermined range, further higher thermal insulation properties can be obtained.
[0095] That is, when the average primary particle size of the nanoparticles is 1 nm or more and 100 nm or less, especially in a temperature range of less than 500° C., it is possible to suppress the convection heat transfer and conduction heat transfer in the heat transfer suppression sheet, and further improve the thermal insulation. In addition, even when compressive stress is applied, the gaps remaining between the nanoparticles and the contacts between the multiple particles can suppress the conduction heat transfer, and the thermal insulation of the heat transfer suppression sheet can be maintained.
[0096] It should be noted that the average primary particle size of the nanoparticles is more preferably 2 nm or more, and further preferably 3 nm or more. On the other hand, the average primary particle size of the nanoparticles is more preferably 50 nm or less, and further preferably 10 nm or less.
[0097] (Inorganic hydrate particles)
[0098] When the inorganic hydrate particles are exposed to heat from the exothermic body and reach a temperature above the thermal decomposition starting temperature, they undergo thermal decomposition, releasing their own crystal water to lower the temperature of the exothermic body and its surroundings, demonstrating a so-called "endothermic effect." In addition, after releasing the crystal water, they become porous and exhibit a heat-insulating effect through countless air pores.
[0099] Specific examples of inorganic hydrates include aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), zinc hydroxide (Zn(OH)2), iron hydroxide (Fe(OH)2), manganese hydroxide (Mn(OH)2), zirconium hydroxide (Zr(OH)2), gallium hydroxide (Ga(OH)3), etc.
[0100] For example, aluminum hydroxide has about 35% of crystal water, and as shown in the following formula, it undergoes thermal decomposition to release crystal water, exhibiting an endothermic effect. Moreover, after releasing the crystal water, it becomes a porous aluminum oxide (Al2O3), which functions as a heat insulator.
[0101] 2Al(OH)3→Al2O3+3H2O
[0102] It should be noted that, as described below, the heat transfer suppression sheet 10 of the present embodiment is suitable for being sandwiched between battery cells, for example, but in a battery cell that has thermal runaway, the temperature rises sharply to more than 200° C., and the temperature continues to rise to around 700° C. Therefore, as inorganic particles, it is preferable to be composed of an inorganic hydrate having a thermal decomposition starting temperature of 200° C. or more.
[0103] Regarding the thermal decomposition starting temperatures of the above-mentioned inorganic hydrates, aluminum hydroxide is about 200°C, magnesium hydroxide is about 330°C, calcium hydroxide is about 580°C, zinc hydroxide is about 200°C, iron hydroxide is about 350°C, manganese hydroxide is about 300°C, zirconium hydroxide is about 300°C, and gallium hydroxide is about 300°C. They all roughly overlap with the temperature range of the rapid temperature rise of the battery cell when thermal runaway occurs, and can effectively suppress the temperature rise. Therefore, they can be said to be preferred inorganic hydrates.
[0104] (Average secondary particle size of inorganic hydrate particles: 0.01 μm or more and 200 μm or less)
[0105] In addition, when inorganic hydrate particles are used as the first inorganic particles, if the average particle size is too large, it takes a certain amount of time for the first inorganic particles (inorganic hydrate) located near the center of the heat transfer suppression sheet 10 to reach their thermal decomposition temperature, so the first inorganic particles near the center of the sheet may not be completely thermally decomposed. Therefore, the average secondary particle size of the inorganic hydrate particles is preferably 0.01 μm to 200 μm, and more preferably 0.05 μm to 100 μm.
[0106] (Particles composed of heat-expandable inorganic material)
[0107] Examples of the thermally expandable inorganic material include vermiculite, bentonite, mica, and perlite.
[0108] (Particles composed of a porous body containing water)
[0109] Specific examples of the hydrous porous body include zeolite, kaolinite, montmorillonite, acid clay, diatomaceous earth, wet silica, dry silica, aerogel, mica, vermiculite and the like.
[0110] (Inorganic hollow sphere)
[0111] The heat insulating material used in the present invention may contain inorganic hollow spheres as the first inorganic particles.
[0112] When the inorganic hollow spheres are included, convection heat transfer or conductive heat transfer of heat in the thermal insulation material can be suppressed in a temperature range lower than 500° C., and the thermal insulation property of the thermal insulation material can be further improved.
[0113] As the inorganic hollow sphere, at least one selected from the group consisting of volcanic ash hollow spheres, silica hollow spheres, fly ash hollow spheres, barite hollow spheres, and glass hollow spheres can be used.
[0114] (Content of inorganic hollow spheres: 60% by mass or less relative to the total mass of the thermal insulation material)
[0115] The content of the inorganic hollow spheres is preferably 60% by mass or less based on the total mass of the thermal insulation material.
[0116] (Average particle size of inorganic hollow spheres: 1 μm or more and 100 μm or less)
[0117] The average particle size of the inorganic hollow spheres is preferably 1 μm or more and 100 μm or less.
[0118] <Second Inorganic Particles>
[0119] In the case of containing 2 kinds of inorganic particles in the heat transfer inhibition sheet, the second inorganic particles are not particularly limited as long as the material, particle size, etc. are different from the first inorganic particles. As the second inorganic particles, inorganic hollow spheres such as oxide particles, carbide particles, nitride particles, inorganic hydrate particles, silicon dioxide nanoparticles, metal oxide particles, microporous particles, hollow silicon dioxide particles, particles made of thermally expandable inorganic materials, particles made of water-containing porous bodies, etc. can be used, and their details are as described above.
[0120] It should be noted that the conduction heat transfer of nanoparticles is extremely small, and even when compressive stress is applied to the heat transfer suppression sheet, excellent thermal insulation can be maintained. In addition, metal oxide particles such as titanium dioxide have a high effect of shielding radiant heat. Furthermore, if large-diameter inorganic particles and small-diameter inorganic particles are used, the small-diameter inorganic particles will enter the gaps between the large-diameter inorganic particles, thereby forming a denser structure, which can improve the heat transfer suppression effect. Therefore, when using, for example, nanoparticles as the above-mentioned first inorganic particles, it is preferred that the heat transfer suppression sheet further contain particles composed of metal oxides having a larger particle size than the first inorganic particles as the second inorganic particles.
[0121] Examples of the metal oxide include silicon oxide, titanium oxide, aluminum oxide, barium titanate, zinc oxide, zircon, zirconium oxide, etc. Titanium oxide (titanium dioxide) is a component with a higher refractive index than other metal oxides, and has a high effect of diffusely reflecting light and shielding radiant heat in a high temperature range of 500° C. or more, so titanium dioxide is most preferably used.
[0122] When at least one particle selected from dry silica particles and silica aerogel is used as the first inorganic particle and at least one particle selected from titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide and aluminum oxide is used as the second inorganic particle, in order to obtain excellent thermal insulation performance in a temperature range of 300° C. or less, the first inorganic particle is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more relative to the total mass of the inorganic particles. In addition, the first inorganic particle is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less relative to the total mass of the inorganic particles.
[0123] On the other hand, in order to obtain excellent thermal insulation performance in a temperature range exceeding 300° C., the second inorganic particles are preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more relative to the total mass of the inorganic particles. In addition, the second inorganic particles are preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less relative to the total mass of the inorganic particles.
[0124] (Average primary particle size of the second inorganic particles)
[0125] When the heat transfer suppressing sheet contains second inorganic particles composed of a metal oxide, if the average primary particle size of the second inorganic particles is 1 μm to 50 μm, radiant heat transfer can be effectively suppressed in a high temperature region of 500° C. or higher. The average primary particle size of the second inorganic particles is more preferably 5 μm to 30 μm, and most preferably 10 μm or less.
[0126] (Content of Inorganic Particles)
[0127] In the present embodiment, if the total content of the inorganic particles 4 in the heat transfer suppression sheet 10 is appropriately controlled, the heat insulating property of the heat transfer suppression sheet 10 can be sufficiently ensured.
[0128] The total content of the inorganic particles 4 is preferably 60% by mass or more, and more preferably 70% by mass or more, relative to the total mass of the heat transfer suppression sheet 10. In addition, if the total content of the inorganic particles 4 is too much, the content of the organic fiber and the inorganic fiber will be relatively reduced. Therefore, in order to fully obtain the reinforcement effect of the skeleton and the retention effect of the inorganic particles, the total content of the inorganic particles 4 is preferably 95% by mass or less, and more preferably 90% by mass or less, relative to the total mass of the heat transfer suppression sheet 10.
[0129] <Inorganic Fiber>
[0130] As the inorganic fiber 15, a single inorganic fiber may be used, or two or more inorganic fibers may be used in combination. Examples of the inorganic fiber include silica fiber, alumina fiber, aluminum silicate fiber, zirconium oxide fiber, carbon fiber, soluble fiber, refractory ceramic fiber, aerogel composite material, magnesium silicate fiber, alkaline earth silicate fiber, potassium titanate fiber, silicon carbide fiber, potassium titanate whisker fiber and other ceramic fibers, glass fiber, glass wool, slag wool and other glass fibers, rock wool, basalt fiber, mullite fiber, and natural mineral fibers such as wollastonite as mineral fibers other than the above.
[0131] These inorganic fibers are preferred from the viewpoint of heat resistance, strength, availability, etc. Among the inorganic fibers, silica-alumina fibers, alumina fibers, silica fibers, rock wool, alkaline earth silicate fibers, and glass fibers are particularly preferred from the viewpoint of handleability.
[0132] The cross-sectional shape of the inorganic fiber is not particularly limited, and examples thereof include circular cross-section, flat cross-section, hollow cross-section, polygonal cross-section, core cross-section, etc. Among them, fibers with a hollow cross-section, flat cross-section or polygonal cross-section with a special cross-section can be appropriately used because they can slightly improve thermal insulation properties.
[0133] The preferred lower limit of the average fiber length of the inorganic fibers is 0.1 mm, and the more preferred lower limit is 0.5 mm. On the other hand, the preferred upper limit of the average fiber length of the inorganic fibers is 50 mm, and the more preferred upper limit is 10 mm. If the average fiber length of the inorganic fibers is less than 0.1 mm, it is not easy for the inorganic fibers to be entangled with each other, and the mechanical strength of the heat transfer suppression sheet 10 may be reduced. On the other hand, if the average fiber length of the inorganic fibers is greater than 50 mm, although a reinforcing effect can be obtained, the inorganic fibers cannot be tightly entangled with each other, or only a single inorganic fiber is rolled up, which easily produces continuous gaps, and thus may lead to a reduction in thermal insulation.
[0134] The preferred lower limit of the average fiber diameter of the inorganic fibers is 1 μm, the more preferred lower limit is 2 μm, and the further preferred lower limit is 3 μm. On the other hand, the preferred upper limit of the average fiber diameter of the inorganic fibers is 15 μm, and the more preferred upper limit is 10 μm. If the average fiber diameter of the inorganic fibers is less than 1 μm, the mechanical strength of the inorganic fibers themselves may be reduced. In addition, from the perspective of the impact on human health, the average fiber diameter of the inorganic fibers is preferably greater than 3 μm. On the other hand, if the average fiber diameter of the inorganic fibers is greater than 15 μm, the solid heat transfer using the inorganic fibers as a medium increases, which may lead to a decrease in thermal insulation, and the formability and strength of the heat transfer suppression sheet may be deteriorated.
[0135] (Inorganic fiber content)
[0136] In the present embodiment, when the heat transfer suppression sheet 10 includes inorganic fibers, the content of the inorganic fibers is preferably 3 mass % or more and 15 mass % or less relative to the total mass of the heat transfer suppression sheet 10 .
[0137] In addition, the content of the inorganic fiber is more preferably 5% by mass or more and 10% by mass or less relative to the total mass of the heat transfer suppression sheet 10. By setting such a content, the shape retention, extrusion resistance, wind pressure resistance, and inorganic particle retention capacity based on the inorganic fiber can be well balanced. In addition, by appropriately controlling the content of the inorganic fiber, the organic fiber 1 and the inorganic fiber are entangled with each other to form a three-dimensional network, thereby further improving the effect of retaining the inorganic particles 4 and other mixed materials described later.
[0138] <Other mixed materials>
[0139] It should be noted that the heat transfer suppression sheet of this embodiment may contain other inorganic fibers, other organic fibers, binding materials, colorants, etc. as needed in addition to the above-mentioned inorganic particles 4, organic fibers 1 and inorganic fibers 15. These are useful for the purpose of strengthening the heat transfer suppression sheet and improving the moldability, etc. The total amount of these mixed materials is preferably 10% by mass or less relative to the total mass of the heat transfer suppression sheet.
[0140] [Method for producing heat transfer suppressing sheet]
[0141] Hereinafter, an example of a method for manufacturing the heat transfer suppression sheet 10 according to the present embodiment will be described.
[0142] For example, a binder fiber (not shown) having a core-sheath structure, the inorganic fibers 15, and the inorganic particles 4 are put into a mixer such as a V-type mixer at a predetermined ratio to prepare a mixture.
[0143] As described above, the binder fiber preferably has a core-sheath structure in which the core is made of a first organic material and the sheath is made of a second organic material. In this case, the melting point of the first organic material is higher than that of the second organic material.
[0144] Thereafter, the obtained mixture is put into a predetermined mold, pressurized by a press machine or the like, and the obtained molded body is heated, whereby the sheath of the binder fiber is melted. Thereafter, by cooling the heated molded body, the melted second organic material constituting the sheath and the inorganic particles 4 present around the binder fiber are fused to the core (organic fiber 1), and the inorganic fibers 15 in contact with the outer peripheral surface of the binder fiber are also fused to the organic fiber 1. In addition, a matrix 14 containing the inorganic particles 4 is formed between the organic fibers 1, between the inorganic fibers 15, and between the organic fibers 1 and the inorganic fibers 15. Thus, a heat transfer suppressing sheet 10 processed into a sheet shape can be obtained.
[0145] It should be noted that when the above mixture is pressurized and heated, the density of the inorganic particles 4 increases, so in the obtained heat transfer suppressing sheet 10, an air layer 18 is formed between the inorganic fibers 15 and the matrix 14. As described above, the air layer 18 can be used to obtain the heat transfer suppressing effect.
[0146] In this embodiment, the heat transfer suppression sheet 10 is preferably manufactured by a dry method. When the dry method is used, inorganic particles 4 suitable for the dry method are used, and a solvent such as water required for molding by a wet method is not added to the above-mentioned mixture. However, when manufacturing the heat transfer suppression sheet 10, in order to prevent the inorganic particles 4 and other powders from flying and making the handling of the raw materials difficult, a small amount of water or other solvents may be added within the range considered as a dry method. For example, by adding a small amount of water or other solvents to the mixture, the scattering of inorganic particles during manufacturing can be suppressed.
[0147] According to the manufacturing method of this embodiment, since the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath, when the mixture is heated, the core can be left and the sheath can be melted. And, after cooling, since the outer peripheral surface of the core (organic fiber 1) is coated with the second organic material containing inorganic particles 4, the inorganic particles 4 can be retained. Since the organic fiber 1 fused with the inorganic particles 4 has an apparently thick fiber diameter, the strength is higher than the strength of the organic fiber 1 alone. In addition, in the mixture, the adhesive fiber and the inorganic fiber 15 exist in irregular directions, and the adhesive fibers may be partially in contact with each other and the adhesive fibers and the inorganic fibers 15. As a result, the organic fibers 1 are fused to each other, and the organic fibers 1 and the inorganic fibers 15 are fused to each other using the fusion portion 5 to form a three-dimensional skeleton. As a result, the overall shape of the heat transfer suppression sheet can be further maintained with high strength.
[0148] It should be noted that even when an organic fiber without a core-sheath structure is used as a binder fiber, it is possible to leave the center of the organic fiber and melt only the surface, so that inorganic particles can be covered on the surface, or the organic fibers can be welded to each other or to the inorganic fibers. However, when manufacturing a heat transfer suppressing sheet, heating is usually performed from one side or both sides orthogonal to the thickness direction. Since a material with high thermal insulation performance is used, strict temperature management is required to increase the temperature to the same level on the surface side and the center side in the thickness direction of the sheet.
[0149] On the other hand, when using a binder fiber having a core-sheath structure in which the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath, it is possible to set a temperature for making the core very easy to remain and for melting the sheath. As a result, in the obtained heat transfer suppressing sheet, both the organic fiber 1 and the inorganic fiber 15 serve as a skeleton for maintaining the strength of the sheet on both the surface side and the center side, and have an ideal structure in which the fusion bond 5 containing the inorganic particles 4 is formed on the surface of the organic fiber 1. Therefore, as a material for the heat transfer suppressing sheet 10, it is preferable to use the binder fiber having the core-sheath structure described above.
[0150] It should be noted that as a raw material for the heat transfer suppression sheet, a binder such as a hot-melt powder may also be contained in the mixture, and the details will be described below. By appropriately adjusting the type and content of the binder contained in the mixture, the organic fiber 1 and the inorganic fiber 15 are fully fixed, and the retention force of the inorganic particles 4 can be improved, and the powder can be further suppressed from falling off.
[0151] As a result, the heat transfer suppression sheet 10 manufactured by the manufacturing method of this embodiment has a stronger skeleton, can maintain its shape even when a pressing force or impact is applied to the heat transfer suppression sheet, can suppress powder falling, and can maintain excellent thermal insulation performance.
[0152] It should be noted that, in order to further suppress the falling of powder, the surface of the heat transfer suppression sheet 10 may be coated with a film or the like. Examples of the polymer film include films made of polyimide, polycarbonate, PET, polyphenylene sulfide, polyetherimide, cross-linked polyethylene, flame retardant chloroprene rubber, polyvinylidene fluoride, rigid vinyl chloride, polybutylene terephthalate, PTFE, PFA, FEP, ETFE, rigid PCV, flame retardant PET, polystyrene, polyethersulfone, polyamide-imide, polyacrylonitrile, polyethylene, polypropylene, polyamide, and the like. It should be noted that there is no particular limitation on the method of coating the surface of the heat transfer suppression sheet 10 with a film, and examples include a method of attaching the heat transfer suppression sheet 10 with an adhesive or the like, a method of wrapping the heat transfer suppression sheet 10 with a film, and a method of housing the heat transfer suppression sheet 10 in a bag-shaped film.
[0153] Next, binder fibers and heating conditions preferably used in the method for producing the heat transfer suppressing sheet of the present embodiment will be described.
[0154] <Binder Fiber>
[0155] In this embodiment, when a core-sheath structured binder fiber is used, there is no particular limitation as long as the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath. As the first organic material constituting the core, at least one selected from polyethylene terephthalate, polypropylene and nylon can be used. In addition, as the second organic material constituting the sheath, at least one selected from polyethylene terephthalate, polyethylene, polypropylene and nylon can be selected.
[0156] If the melting point of the first organic material constituting the core is sufficiently higher than the melting point of the second organic material constituting the sheath, the setting margin of the heating temperature in the heating process can be expanded, and the temperature setting for obtaining a further desired structure can be made easier. For example, the melting point of the first organic material is preferably higher than the melting point of the second organic material by 60°C or more, more preferably higher by 70°C or more, and further preferably higher by 80°C or more.
[0157] It should be noted that the above-mentioned adhesive fiber with a core-sheath structure is generally commercially available, and the materials constituting the core and the sheath may be the same or different from each other. Examples of adhesive fibers in which the core and the sheath are made of the same material and have different melting points include, for example, a case where the core and the sheath are made of polyethylene terephthalate, a case where they are made of polypropylene, and a case where they are made of nylon. Examples of adhesive fibers in which the core and the sheath are made of different materials include a case where the core is made of polyethylene terephthalate and the sheath is made of polyethylene; a case where the core is made of polypropylene and the sheath is made of polyethylene, and the like.
[0158] In this embodiment, the melting point of the second organic material constituting the sheath of the binder fiber means the melting temperature at which the second organic material starts to melt and deform, and softening accompanied by shape change is also considered as one type of melting and deformation. The melting point of the sheath of the binder fiber can be measured, for example, by the following method.
[0159] The binder fiber to be measured is arranged in such a manner as to be in contact with the glass fiber having a higher melting point, and is heated from room temperature to, for example, 200°C at a heating rate of 5°C / min, and then cooled to room temperature. At this time, if the surface of the binder fiber undergoes melting deformation and fusion occurs at the portion in contact with the glass fiber, or if the cross-sectional shape of the binder fiber changes, it can be determined that the melting point of the second organic material constituting the sheath portion is 200°C or less. In this embodiment, the heating temperature is varied, and the fusion state of the binder fiber and the glass fiber after cooling or the cross-sectional shape of the binder fiber is observed by the above method, thereby determining the melting point of the second organic material constituting the sheath portion.
[0160] (Content of Binder Fiber)
[0161] In the present embodiment, when a core-sheath structured binder fiber is used as a material, if the content of the binder fiber in the mixture is appropriately controlled, a sufficient reinforcing effect of the skeleton can be obtained in the obtained heat transfer suppressing sheet 10 .
[0162] The content of the binder fiber is preferably 5% by mass or more, more preferably 10% by mass or more, relative to the total mass of the mixture. In addition, if the content of the binder fiber is too much, the content of the inorganic particles 4 is relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of the binder fiber is preferably 25% by mass or less, more preferably 20% by mass or less, relative to the total mass of the mixture.
[0163] <Thermo-fusible powder>
[0164] In this embodiment, in addition to the above-mentioned binder fibers, inorganic fibers 15 and inorganic particles 4, the mixture may further contain a hot-melt powder. The hot-melt powder is, for example, a powder containing a third organic material different from the above-mentioned first organic material and second organic material and having the property of melting by heating. By adding the hot-melt powder to the mixture and heating it, the hot-melt powder melts, and when it is cooled thereafter, it solidifies in a state containing the surrounding inorganic particles 4, inorganic fibers 15, etc. Therefore, it is possible to further suppress the inorganic particles 4 from falling off from the heat transfer suppression sheet 10.
[0165] As the hot-melt powder, there are hot-melt powders with various melting points, but it is sufficient to select a hot-melt powder with an appropriate melting point in consideration of the melting points of the core and sheath of the binder fiber used. Specifically, if the third organic material as a component constituting the hot-melt powder has a lower melting point than the first organic material constituting the organic fiber, it is possible to set a heating temperature for melting the sheath and the hot-melt powder while leaving the core. For example, if the melting point of the hot-melt powder is lower than the melting point of the sheath, the heating temperature during manufacturing can be set between the melting point of the core and the melting point of the sheath, so that the heating temperature can be set more easily.
[0166] On the other hand, the type of hot-melt powder used can also be selected in such a way that the melting point of the hot-melt powder is between the melting point of the core and the melting point of the sheath. When using a hot-melt powder with such a melting point, after the sheath and the hot-melt powder are melted, when they are cooled and solidified, the hot-melt powder existing in the gap between the organic fiber (core) 1 and the surrounding molten sheath, inorganic fiber 15 and inorganic particles 4 solidifies first. As a result, the positions of the organic fiber 1 and the inorganic fiber 15 can be fixed, and then by welding the molten sheath to the organic fiber, a three-dimensional skeleton can be easily formed. Therefore, the strength of the entire sheet can be further improved.
[0167] If the melting point of the third organic material constituting the hot-melt powder is sufficiently lower than the melting point of the first organic material constituting the core, the setting margin of the heating temperature in the heating process can be expanded, and the temperature setting for obtaining a further desired structure can be made easier. For example, the melting point of the first organic material is preferably higher than the melting point of the third organic material by 60°C or more, more preferably higher by 70°C or more, and further preferably higher by 80°C or more.
[0168] It should be noted that the melting point of the hot-melt powder (third organic material) is preferably 80° C. or higher, more preferably 90° C. or higher. In addition, the melting point of the hot-melt powder (third organic material) is preferably 180° C. or lower, more preferably 150° C. or lower. Components constituting the hot-melt powder include polyethylene, polyester, polyamide, ethylene vinyl acetate, and the like.
[0169] (Content of hot-melt powder)
[0170] In order to suppress the falling of inorganic particles, when the mixture contains a hot-melt powder, even a trace amount thereof can obtain the effect of suppressing the falling of powder. Therefore, the content of the hot-melt powder is preferably 0.5% by mass or more, more preferably 1% by mass or more relative to the total mass of the mixture.
[0171] On the other hand, if the content of the hot-melt powder is increased, the content of the inorganic particles 4 etc. will be relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of the hot-melt powder is preferably 5% by mass or less, more preferably 4% by mass or less relative to the total mass of the mixture.
[0172] <Heating conditions>
[0173] As the process of processing the above-mentioned mixture into a sheet, there can be cited a process of pressurizing the mixture and a process of heating the mixture. In the case of using a core-sheath structured binder fiber as the material of the heat transfer suppressing sheet 10, the heating temperature in the heating process is preferably a temperature higher than the melting point of the second organic material constituting the sheath and lower than the melting point of the first organic material constituting the core. By setting such a heating temperature, as described above, the strength of the sheet can be ensured by the core on either side of the surface side or the center side of the sheet, and the inorganic particles 4 can be retained by the fusion portion 5.
[0174] Specifically, the heating temperature in the heating step is preferably set to be higher than the melting point of the second organic material constituting the sheath by 10° C. or more, and more preferably higher than 20° C. or more. On the other hand, the heating temperature is preferably set to be lower than the melting point of the first organic material constituting the core by 10° C. or more, and more preferably lower than 20° C. or more.
[0175] The heating time is not particularly limited, but is preferably set to a heating time that allows the sheath portion to be sufficiently melted, and can be set, for example, to a time of 3 minutes to 15 minutes.
[0176] In the case of including a hot-melt powder as the material of the heat transfer suppressing sheet, the heating temperature in the heating process is preferably set to be 10°C or higher than the higher one of the melting point of the second organic material constituting the sheath and the melting point of the third organic material constituting the hot-melt powder, and more preferably set to be 20°C or higher. On the other hand, the heating temperature is preferably set to be 10°C or lower than the melting point of the first organic material constituting the core, and more preferably set to be 20°C or lower. By setting the heating temperature to such a temperature, a strong skeleton can be formed, the strength of the sheet can be further improved, and the inorganic particles 4 can be prevented from falling off by the fusion portion 5 and the like.
[0177] <Thickness of Heat Transfer Suppression Sheet>
[0178] The thickness of the heat transfer suppression sheet of this embodiment is not particularly limited, and is preferably 0.05 mm or more and 10 mm or less. If the thickness is 0.05 mm or more, sufficient compressive strength can be obtained. On the other hand, if the thickness is 10 mm or less, good thermal insulation of the heat transfer suppression sheet can be obtained.
[0179] [Battery Pack]
[0180] An example of a battery pack to which the heat transfer suppressing sheet 10 according to an embodiment of the present invention is applied is as described above. Figure 3 Here, we use Figure 3 The configuration and effects of the battery pack are described in detail.
[0181] like Figure 3 As shown, the battery pack 100 includes a plurality of battery cells 20 a , 20 b , and 20 c and a heat transfer suppressing sheet according to the present embodiment, and the plurality of battery cells are connected in series or in parallel.
[0182] For example, Figure 3 As shown, the heat transfer suppression sheet 10 of this embodiment is interposed between the battery cells 20a and 20b and between the battery cells 20b and 20c. The battery cells 20a, 20b, 20c and the heat transfer suppression sheet 10 are housed in a battery case 30.
[0183] In addition, the heat transfer suppressing sheet 10 is as described above.
[0184] In the battery pack 100 configured in this way, even if a battery cell 20a reaches a high temperature, the heat transfer suppressing sheet 10 having a heat transfer suppressing effect is present between the battery cell 20a and the battery cell 20b, thereby suppressing the heat transfer to the battery cell 20b.
[0185] In addition, since the heat transfer suppression sheet 10 of this embodiment has high compressive strength, it is possible to suppress the thermal expansion of the battery cells 20a, 20b, and 20c even during the charge and discharge of the battery cells. Therefore, the distance between the battery cells can be ensured, excellent thermal insulation performance can be maintained, and thermal runaway of the battery cells can be prevented. In addition, since it has the effect of suppressing the shedding of powder, it can be easily handled.
[0186] It should be noted that the battery pack 100 of this embodiment is not limited to Figure 3 For example, the heat transfer suppression sheet 10 is not only disposed between the battery cells 20a and 20b, and between the battery cells 20b and 20c, but also disposed between the battery cells 20a, 20b, 20c and the battery case 30, or attached to the inner surface of the battery case 30.
[0187] In the battery pack 100 configured in this manner, when a battery cell catches fire, it is possible to suppress the flame from spreading to the outside of the battery case 30 .
[0188] For example, the battery pack 100 of the present embodiment may be used in an electric vehicle (EV) or the like and may be placed under the floor of a passenger. In this case, even if a battery cell catches fire, the safety of the passenger can be ensured.
[0189] In addition, since the heat transfer suppression sheet 10 is not only sandwiched between the battery cells but can also be arranged between the battery cells 20a, 20b, 20c and the battery case 30, there is no need to newly produce fireproof materials, etc., and a safe battery pack 100 can be easily constructed at low cost.
[0190] In the battery pack of this embodiment, the heat transfer suppression sheet 10 disposed between the battery cells 20a, 20b, 20c and the battery case 30 may be in contact with the battery cells or may have a gap therebetween. However, if there is a gap between the heat transfer suppression sheet 10 and the battery cells 20a, 20b, 20c, even if the temperature of any one of the plurality of battery cells rises and the volume expands, deformation of the battery cell can be tolerated.
[0191] It should be noted that the heat transfer suppression sheet 10 of this embodiment can be made into various shapes according to its manufacturing method. Therefore, it can cope with any shape without being affected by the shape of the battery cells 20a, 20b, 20c and the battery case 30. Specifically, in addition to square batteries, it can also be applied to cylindrical batteries, flat batteries, etc.
[0192] Various embodiments have been described above, but the present invention is certainly not limited to such examples. Those skilled in the art can certainly think of various variations or modifications within the scope described in the claims, and it should be understood that they also belong to the technical scope of the present invention. In addition, the various constituent elements in the above embodiments can also be arbitrarily combined within the scope of the invention without departing from the gist of the invention.
[0193] It should be noted that the present application is based on the Japanese patent application (Japanese Patent Application No. 2022-086810) filed on May 27, 2022, and its contents are incorporated herein by reference.
[0194] Explanation of symbols
[0195] 1. Organic Fiber
[0196] 4Inorganic particles
[0197] 5. Welding section
[0198] 10Heat transfer suppression sheet
[0199] 14 Matrix
[0200] 15Inorganic fiber
[0201] 18 air layers
[0202] 20a, 20b, 20c battery cells
[0203] 30 battery case
[0204] 100 battery pack
Claims
1. A heat transfer suppressing sheet comprising a matrix containing inorganic particles, inorganic fibers dispersed in the matrix, and organic fibers, wherein: The organic fibers and the inorganic fibers are interwoven with each other to form a three-dimensional network structure.
2. The heat transfer suppressing sheet according to claim 1, wherein: The substrate has an air layer around the inorganic fibers.
3. The heat transfer suppressing sheet according to claim 1, wherein: The organic fibers have a fusion bond portion covering at least a portion of a surface, and at least a portion of the inorganic fibers is fused to the organic fibers via the fusion bond portion.
4. The heat transfer suppressing sheet according to claim 3, wherein: At least a portion of the inorganic particles is fused to the organic fibers through the fusion portion.
5. The heat transfer suppressing sheet according to claim 3, wherein: The organic fibers are formed of a first organic material, and the fusion bond includes a second organic material having a melting point lower than that of the first organic material.
6. The heat transfer suppressing sheet according to claim 5, wherein: The melting point of the second organic material is lower than that of the first organic material by at least 60° C.
7. The heat transfer suppressing sheet according to claim 5, wherein: The first organic material is at least one selected from polyethylene terephthalate, polypropylene and nylon, and the second organic material is at least one selected from polyethylene terephthalate, polyethylene, polypropylene and nylon.
8. The heat transfer suppressing sheet according to claim 1, wherein: The inorganic particles include at least one particle selected from oxide particles, carbide particles, nitride particles, and inorganic hydrate particles.
9. The heat transfer suppressing sheet according to claim 8, wherein: The inorganic particles include at least one particle selected from the group consisting of dry silica particles and silica aerogels.
10. The heat transfer suppressing sheet according to claim 9, wherein: The inorganic particles further include particles composed of at least one inorganic material selected from the group consisting of titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide, and aluminum oxide.
11. The heat transfer suppressing sheet according to claim 1, wherein: The inorganic fiber is at least one fiber selected from the group consisting of silica-alumina fiber, alumina fiber, silica fiber, rock wool, alkaline earth silicate fiber and glass fiber. 12 . A battery pack comprising a plurality of battery cells and the heat transfer suppressing sheet according to claim 1 , wherein the plurality of battery cells are connected in series or in parallel.
Citation Information
Patent Citations
Heat insulation sheet for battery pack and battery pack
JP2021034278A
Control device for vehicle
JP2022086810A